2011
DOI: 10.1002/btpr.745
|View full text |Cite
|
Sign up to set email alerts
|

Use of computational fluid dynamics as a tool for establishing process design space for mixing in a bioreactor

Abstract: The concept of "design space" plays an integral part in implementation of quality by design for pharmaceutical products. ICH Q8 defines design space as "the multidimensional combination and interaction of input variables (e.g., material attributes) and process parameters that have been demonstrated to provide assurance of quality. Working within the design space is not considered as a change. Movement out of the design space is considered to be a change and would normally initiate a regulatory post-approval ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…Leverage plots can be used for identifying the impact of each process variable as well as interaction among them on the related performance parameters. Finally, optimization function using counter profiler can be used by setting constraints on the response variables as per the process needs to estimate the "design space" [13,14].…”
Section: Actual Vs Predicted Graphs Leverage Plotsmentioning
confidence: 99%
“…Leverage plots can be used for identifying the impact of each process variable as well as interaction among them on the related performance parameters. Finally, optimization function using counter profiler can be used by setting constraints on the response variables as per the process needs to estimate the "design space" [13,14].…”
Section: Actual Vs Predicted Graphs Leverage Plotsmentioning
confidence: 99%
“…Even though the selection of single average bubble size across the vessel, via a couple discrete phase model (DPM), can easily create matching values versus experimental data, it is preferred to use population balance equations to reflect bubble breakage and coalescence, which is closer to a real case scenario with a broad bubble size distribution [91]. Rathore et al showed that without the application of the population balance method, the simulation result can be misleading, yielding very high gas volume fractions at the top of tank [92]. In addition, their work showed that mass transfer rate is more than tenfold higher in the impeller zone versus other zones in the bulk liquid.…”
Section: Computational Fluid Dynamics (Cfd) Simulationsmentioning
confidence: 97%
“…In essence, it is the interplay between input variable and process parameters and the resulting impact on critical quality attributes of a product. Rathore et al [28] have presented the utility of CFD modeling in defining the design space for mixing in a bioreactor for drug substance manufacturing. The authors have modeled the flow profiles in a small-scale aerated bioreactor through CFD modeling and have demonstrated its utility for evaluating the effects of process parameters including impeller speed, gas flow rate and liquid height on the mass transfer coefficient.…”
Section: Application Of Modeling Approaches For Biologic Drug Productmentioning
confidence: 99%
“…The key assumption being that the flow profiles at small scale have been modeled through CFD and correlation to manufacturing scale vessel is established. The total shear stress experienced by the protein as a function of various factors (either determined based on operation range of the manufacturing vessel or allowed to float freely) at the actual manufacturing scale can then be modeled via CFD to determine the adequate design space that maintains the total shear within the bounds of the permissible range [28,31]. Alternatively, an edge of failure with respect to shear rate can be established at the small scale through lab studies which can subsequently be correlated to manufacturing scale through CFD simulation in order to establish bounds of the operating range for process parameters.…”
Section: Application Of Modeling Approaches For Biologic Drug Productmentioning
confidence: 99%
See 1 more Smart Citation